Facial Nerve Recovery in KbDb and C1q Knockout Mice: A Role for Histocompatibility Complex 1. Issue 12 (December 2016) - Akdagli, Seden; Williams, Ryan A.; Kim, Hyun J.; Yan, Yuling; Mustapha, Mirna; Most, Sam P.
Abstract : Background: Understanding the mechanisms in nerve damage can lead to better outcomes for neuronal rehabilitation. The purpose of our study was to assess the effect of major histocompatibility complex I deficiency and inhibition of the classical complement pathway (C1q) on functional recovery and cell survival in the facial motor nucleus (FMN) after crush injury in adult and juvenile mice. Methods: A prospective blinded analysis of functional recovery and cell survival in the FMN after a unilateral facial nerve crush injury in juvenile and adult mice was undertaken between wild-type, C1q knockout (C1q−/−), and KbDb knockout (KbDb−/−) groups. Whisker function was quantified to assess functional recovery. Neuron counts were performed to determine neuron survival in the FMN after recovery. Results: After facial nerve injury, all adult wild-type mice fully recovered. Juvenile mice recovered incompletely corresponding to a greater neuron loss in the FMN of juveniles compared with adults. The C1q−/− juvenile and adult groups did not differ from wild type. The KbDb−/− adults demonstrated 50% recovery of whisker movement and decreased cell survival in FMN. The KbDb−/− juvenile group did not demonstrate any difference from control group. Conclusion: Histocompatibility complex I plays a role for neuroprotection and enhanced facial nerve recovery in adult mice. Inhibition of the classical complement pathway alone does not affect functional recovery or neuronal survival. The alternative and mannose binding pathways pose alternative means for activating the final components of the pathway that may lead to acute nerve damage.